Analysis of the History Learning Model Based on Higher Order Thinking Skills (HOTS) in the Merdeka Curriculum - Muh Ridwan Musyaffa; Atno Atno (STKIP Taman Siswa Bima, 2025)
This study examines the implementation of a Higher Order Thinking Skills (HOTS)-based history learning model within the framework of the Merdeka Curriculum to overcome the dominance of rote learning that still prevalent in history education practices of history education in Indonesia. This study uses a library research approach with a Systematic Literature Review (SLR) framework to analyze the literature related to the implementation of three learning models: Inquiry Based Learning (IBL), Problem Based Learning (PBL), and Project Based Learning (PjBL) in history learning. Relevant publications were analyzed using thematic content analysis techniques with source triangulation to ensure the validity of the findings. The results showed that the three learning models proved effective in improving students' higher-order thinking skills in the domains of analysis, evaluation, and creation through historical information retrieval activities, complex historical problem solving, and project creation in learning. However, the implementation faces major obstacles in the form of limited teacher readiness in designing HOTS instruments, inadequate technological infrastructure, and suboptimal policy support. The research concludes that the implementation of the HOTS model requires a systemic approach through continuous teacher capacity building, digital infrastructure development, and alignment of assessment policies that support the transformation of history learning towards a critical and creative thinking paradigm.